Multidrug-resistant and extensively drug-resistant tuberculosis: a review - Chan, Edward D; Iseman, Michael D (Current opinion in infectious diseases, 2008)
The spread of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant TB (XDR-TB) is a major medical and public health concern for the world. These two forms of highly drug-resistant TB threaten to make TB into an untreatable and highly fatal disease, particularly in resource-poor countries with a high prevalence of AIDS. The focus of this review is to highlight the current extent of the problem. There is a great variability in clinical outcomes for MDR-TB, in part due to differences in the definitions of outcome measures and retrospective nature of the studies. Outcomes for XDR-TB are uniformly worse than those for MDR-TB. A multifaceted approach is needed to prevent a more widespread epidemic of MDR-TB and XDR-TB. Rapid diagnostic assays to detect highly drug-resistant TB are essential in preventing delays in treatment of MDR-TB and XDR-TB and curbing their spread. Development of new drugs to effectively treat all forms of TB in a shorter period of time is urgently needed.